SNX27, a protein involved in down syndrome, regulates GPR17 trafficking and oligodendrocyte differentiation. Issue 8 (6th June 2016) - Meraviglia, Veronica; Ulivi, Alessandro Francesco; Boccazzi, Marta; Valenza, Fabiola; Fratangeli, Alessandra; Passafaro, Maria; Lecca, Davide; Stagni, Fiorenza; Giacomini, Andrea; Bartesaghi, Renata; Abbracchio, Maria P.; Ceruti, Stefania; et al.
Abstract : The G protein‐coupled receptor 17 (GPR17) plays crucial roles in myelination. It is highly expressed during transition of oligodendrocyte progenitor cells to immature oligodendrocytes, but, after this stage, it must be down‐regulated to allow generation of mature myelinating cells. After endocytosis, GPR17 is sorted into lysosomes for degradation or recycled to the plasma membrane. Balance between degradation and recycling is important for modulation of receptor levels at the cell surface and thus for the silencing/activation of GPR17‐signaling pathways that, in turn, affect oligodendrocyte differentiation. The molecular mechanisms at the basis of these processes are still partially unknown and their characterization will allow a better understanding of myelination and provide cues to interpret the consequences of GPR17 dysfunction in diseases. Here, we demonstrate that the endocytic trafficking of GPR17 is mediated by the interaction of a type I PDZ‐binding motif located at the C‐terminus of the receptor and SNX27, a recently identified protein of the endosome‐associated retromer complex and whose functions in oligodendrocytes have never been studied. SNX27 knock‐down significantly reduces GPR17 plasma membrane recycling in differentiating oligodendrocytes while accelerating cells' terminal maturation. Interestingly, trisomy‐linked down‐regulation of SNX27 expression in the brain of Ts65Dn mice, a model of Down syndrome, correlates with a decrease in GPR17 + cells and an increase in mature oligodendrocytes, which, however, fail in reaching full maturation, eventually leading to hypomyelination. Our data demonstrate that SNX27 modulates GPR17 plasma membrane recycling and stability, and that disruption of the SNX27/GPR17 interaction might contribute to pathological oligodendrocyte differentiation defects. GLIA 2016. GLIA 2016;64:1437–1460 Main Points: SNX27 modulates membrane recycling of GPR17 In maturing oligodendrocytes (OLs) SNX27 down‐regulation triggers degradation of GPR17 and accelerates myelination SNX27, GPR17 expression and OL maturation are altered in a model of Down syndrome